2018
DOI: 10.1007/s00103-018-2838-4
|View full text |Cite
|
Sign up to set email alerts
|

Strukturierte Befragung von Kindern bei Kindeswohlgefährdung: Die deutsche Version des NICHD-Interviewprotokolls in seiner revidierten Fassung

Abstract: Exploration des Kindes bei Verdacht auf Kindeswohlgefährdung Barrieren der Aussagebereitschaft Bei Verdacht auf Kindeswohlgefährdung verhaltensichviele Kinderim Rahmeneiner Befragung zurückhaltend und scheuen sich, einen Missbrauch durch Eltern und Bezugspersonen mitzuteilen [1]. In einer israelischen Studie offenbarten nur 12 % der Vorschulkinder einen vermuteten (nicht eindeutig begründeten) innerfamiliären sexuellen Missbrauch [2]. Mindestens zwei übergeordnete Gründe können der Aussagebereitschaft des Kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Furthermore, since participants were recruited throughout Germany, the official translated German version of the R-NICHD protocol was used to extract the examples for each technique ( Noeker and Franke, 2018 ). The wording of the techniques was adapted to adult recipients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, since participants were recruited throughout Germany, the official translated German version of the R-NICHD protocol was used to extract the examples for each technique ( Noeker and Franke, 2018 ). The wording of the techniques was adapted to adult recipients.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, recent research has shown the significance of including cultural and contextual aspects in the translation process when it comes to the translation of investigative interview protocols for children (IIPCs) as compared to a mere direct translation process ( Navarro et al, 2019 ). Upon reading the official German translation of the R-NICHD protocol ( Noeker and Franke, 2018 ), which was used in this study, some translations appeared to be either sub-optimal or too complicated due to the grammatical structure of some translated statements when compared to the English R-NICHD protocol. Therefore, future research should address whether the translation of the (German) R-NICHD protocol needs to be reassessed and possibly improved.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…Besonders deutlich tritt die Divergenz zu den "Mindestanforderungen" bei Fragen hervor, die sowohl von psychologischen als auch von medizinischen Sachverständigen begutachtet werden können. Beispielsweise empfehlen im Hinblick auf die, keinem Fachgebiet eindeutig zuzuordnende Exploration von Kindern zu im Raum stehenden Gefährdungsereignissen die "Mindestanforderungen" nur sehr allgemein eine Exploration beteiligter Kinder (s. u. S. 12), während die für den medizinischen Bereich geltende Kinderschutzleitlinie (AWFM 2019, S. 202 f.) einen deutlichen Imperativ formuliert, strukturierte Explorationsverfahren, wie etwa das revidierte NICHD Protokoll (Noeker & Franke 2018) einzusetzen, das auch näher erläutert wird. Der Bindungsgrad solcher Leitlinien hängt vom Evidenzgrad ab.…”
Section: Qualitätsbegriffeunclassified